Adoption of Scaled Agile Framework® : A case study - Danska, Pia (My University, 2023)
Agile methods initially designed for single agile teams have gained interest also among large IT organization, because of the increasing pressure of business agility in the market. However, large-scale agile adoption is more complex than agile at team level. Therefore, several frameworks for large-scale agile have been created. Scaled Agile Framework® (SAFe®) is the most popular of those frameworks. This thesis is a qualitative case study that aims to find out how SAFe® was adopted in the case organization, what benefits and challenges were identified and what are the success factors of SAFe® in product development. The case organization is a Finnish business unit in a global IT and business consulting services company. The business unit has around 500 employees and it consists of four departments each of them developing and offering different software products or services for private and public sector organizations. All departments have distributed teams having members in Finland and India and one department also in Estonia. Data was collected from documentation and five semi-structured interviews of Release Train Engineers (RTEs) representing five of six Agile Release Trains (ARTs) in the case organization. Additionally, researcher’s reflection on the experience in benefits, challenges and success factors as a representative of one of the six ARTs is included separately from the results of the interviews. The results of this study support the existing knowledge in this research area. Large-Scale Agile transformation is challenging process demanding invest in time, resources, training, coaching and change management. Management support is also important to succeed in transformation. SAFe® is a large framework and there is no one-size-fits-all way to implementation. Step-by-step implementation, continuous learning and improving over time may help to find the best fit for the organization. All ARTs identified benefits, challenges and success factors. Top benefits are systematic way of working/structure, predictability and transparency/visibility. Top challenges are adoption approach, large/heavy framework and product/backlog management. Top success factors are PI Planning, customization of SAFe®, step-by-step implementation and methods for continuous improvement. New findings were identified in all categories. New benefits are metrics, product roadmap has evolved and increased commitment in delivery. New challenges are multiple roles, unplanned work and knowledge silos. Capacity allocation, adequate data in agile project management tool, Definition of Ready, efficient prioritization and Innovation and Planning iteration were identified as new success factors. Identified SAFe® practices as success factors are PI Planning, Capacity allocation, Definition of Ready and Innovation and Planning iteration.

Ketterän kehittämisen menetelmät on alun perin suunnattu yksittäisille tiimeille. Markkinoiden nopeasti muuttuvat vaatimukset edellyttävät IT-organisaatioilta nopeaa reagointikykyä, minkä vuoksi myös isot ja keskisuuret tuotekehitysorganisaatiot ovat kiinnostuneet ottamaan ketterän kehittämisen menetelmiä ja malleja käyttöön. Isoissa organisaatioissa ketterien menetelmien käyttöönotto on monimutkaisempaa, mistä syystä keskisuuria ja isoja organisaatioita varten on kehitetty skaalattuja ketterien menetelmien viitekehyksiä, kuten Scaled Agile Framework® (SAFe®), joka on näistä suosituin. Tämä tutkielma on tapaustutkimus, joka pyrkii selvittämään, miten SAFe® on käyttöönotettu erään globaalin IT konsultointiyrityksen yhdessä suomalaisessa liiketoimintayksikössä. Tutkimuksessa kartoitetaan, mitä SAFe®:n tuomia hyötyjä, haasteita ja menestystekijöitä kyseisessä yksikössä on tunnistettu. Liiketoimintayksikössä on noin 500 työntekijää ja se koostuu neljästä osastosta, jotka kehittävät ja tarjoavat erilaisia ohjelmistotuotteita ja –palveluita yksityiselle ja julkiselle sektorille. Kaikilla osastoilla tiimit ovat erillään Suomessa ja Intiassa sekä yhden osaston osalta myös Virossa. Tutkimuksessa käytetty tieto on kerätty dokumentaatiosta sekä viiden Release Train Engineer:in (RTE) puolistrukturoidusta haastattelusta. RTE:t edustavat viittä Agile Release Train:ia (ART) kuudesta. Lisäksi tutkijan oma reflektointi hyödyistä, haasteista ja menestystekijöistä yhden ART:n edustajana on esitetty haastattelutuloksista erillään. Tulokset vastaavat aiempia löydöksiä tutkimusalueelta. Ketterän kehittämisen skaalaamisen edellyttämä muutos on työläs prosessi, joka vaatii aikaa, resursseja, koulutusta, valmennusta ja muutosjohtamista. Johtajien tuki muutoksessa on tärkeä. SAFe® on laaja viitekehys, jonka käyttöönotto vaatii sovittamista organisaation tarpeisiin ja toimintaan vaiheittain jatkuvan oppimisen ja parantamisen kautta. Kaikki ART:t tunnistivat joitain hyötyjä, haasteita ja menestystekijöitä. Hyödyistä tunnistetuimmat ovat systemaattinen tapa työskennellä/rakenne, ennustettavuus sekä läpinäkyvyys/näkyvyys. Haasteista tunnistetuimmat ovat käyttöönottotapa, laaja/raskas viitekehys sekä tuote-/työjonon hallinta. Tunnistetuimmat menestystekijät ovat PI-suunnittelu, SAFe®:n kustomointi, vaiheittainen käyttöönotto sekä jatkuvan parantamisen menetelmät. Kaikista kategorioista tuli myös uusia löydöksiä. Uusia tunnistettuja hyötyjä ovat mittarit, tuotteen tiekartta on kehittynyt ja sitoutuminen toimitukseen on kasvanut. Uusia haasteita ovat monet roolit, suunnittelematon työ ja osaamissiilot. Uusia menestystekijöitä ovat kapasiteettivaraukset, riittävä tieto projektinhallintatyökalussa, Definition of Ready (DOR), tehokas priorisointi sekä Innovation and Planning –iteraatio. SAFe®:n käytännöistä tunnistettuja menestystekijöitä ovat PI Planning, Capacity allocation, Definition of Ready and Innovation and Planning iteration.
Keywords: Scaled Agile Framework®, SAFe®, scaled agile, large-scale agile, agile adoption, agile transformation, agile implementation